'n Estetika van Televisievermaak - Pieter Jacobus Fourie (Communicare)
AGAINST the background of the indefinability of entertainment the author postulates a for questions that the researcher could ask in connection with the viewer's aesthetic exparience of television entertainment, par ticularly related to television fiction. The central question is: why and how does television entertain the viewer? This question leads on to the following questions: what is entertainment? The answer is that it is in definable. In the style of Plato the researcher should then ask the following: but what is it that leads the viewer to attach the value "entertainment", which is associated with pleasure and satisfaction, to television fic tion? Possible answer: catharsis due to the ability and needs of the viewer to identify with a make-believe world and characters. What makes this identification possible? Amongst other possibilities specific rhetorical motifs which have always been associated with communication pleasure and which are also present in the content (and forum) of television fiction. Is this the big answer? No. The aesthetic experience of a work (also of television) does not allow it to be described easily.